2021
DOI: 10.3390/ijms222212603
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Lipid Oxidation and Ferroptosis to Radiotherapy Efficacy

Abstract: Radiotherapy promotes tumor cell death and senescence through the induction of oxidative damage. Recent work has highlighted the importance of lipid peroxidation for radiotherapy efficacy. Excessive lipid peroxidation can promote ferroptosis, a regulated form of cell death. In this review, we address the evidence supporting a role of ferroptosis in response to radiotherapy and discuss the molecular regulators that underlie this interaction. Finally, we postulate on the clinical implications for the intersectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 76 publications
2
8
0
Order By: Relevance
“…Additionally, ferroptosis levels were higher in response/sensitive tumor cases/cells under chemotherapy or radiotherapy treatment (Figures 6D-F). These findings are consistent with the studies in CESC that silencing components of ferroptosis signaling leads to radiotherapy resistance (40,41). A prior study also showed that the chemosensitizing effects of Andrographis were mediated by activation of ferroptosis (42).…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, ferroptosis levels were higher in response/sensitive tumor cases/cells under chemotherapy or radiotherapy treatment (Figures 6D-F). These findings are consistent with the studies in CESC that silencing components of ferroptosis signaling leads to radiotherapy resistance (40,41). A prior study also showed that the chemosensitizing effects of Andrographis were mediated by activation of ferroptosis (42).…”
Section: Discussionsupporting
confidence: 91%
“…The analyses reveal a notable increase in lipid peroxidation for the cell lines treated with RT alone. These results were expected, as lipid peroxidation induced by RT has been reported [ 41 ]. Interestingly, however, the levels of lipid peroxidation induced by NBTXR3 + RT is significantly higher in most cell lines tested, compared to RT alone.…”
Section: Resultssupporting
confidence: 84%
“…By analyzing the expression profile changes upon the knockdown of FTO expression in cells, we identified that some of the deregulated genes were involved in the regulation of lipoproteins, lipid transport, palmitate, and monooxygenase, all of which are hallmarks of ferroptosis. Previous studies have shown that radiotherapy directly induces ferroptosis by upregulating critical regulators of ferroptosis, including SLC7A11 and ACSL4, in cancer cells [32] . Thus, we explored the regulatory relationship between FTO and ferroptosis in NPC radioresistance.…”
Section: Discussionmentioning
confidence: 98%